2010
DOI: 10.5009/gnl.2010.4.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Long-Term Outcome of Endoscopic Treatment of Sporadic Nonampullary Duodenal Adenoma

Abstract: Background/Aims: Endoscopic resection has proven to be a safe and effective alternative to surgery for duodenal adenomas. However, few data are available on the adequacy of resection and long-term outcomes. This study evaluated the efficacy and longterm endoscopic findings in a cohort of Korean patients who underwent endoscopic mucosal resection (EMR) of sporadic duodenal adenomas. Methods: Seventeen patients with nonampullary duodenal adenomas without familial polyposis syndrome and who were treated by EMR be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 26 publications
3
27
0
1
Order By: Relevance
“…Early bleeding has been the most frequently observed complication, occurring in up to 33% of patients (Tables 3 and 4). 10,28,29,40,[44][45][46][47][48][49][50][51][52] The number of patients enrolled in these studies is limited because of the low prevalence of these lesions and also because large lesions were treated surgically. 1,11,12 53,54 The American Society for Gastrointestinal Endoscopy guidelines suggest considering surgical resection for duodenal lesions that involve Ͼ33% of the luminal circumference, because of the difficulty of radical endoscopic removal.…”
Section: Discussionmentioning
confidence: 99%
“…Early bleeding has been the most frequently observed complication, occurring in up to 33% of patients (Tables 3 and 4). 10,28,29,40,[44][45][46][47][48][49][50][51][52] The number of patients enrolled in these studies is limited because of the low prevalence of these lesions and also because large lesions were treated surgically. 1,11,12 53,54 The American Society for Gastrointestinal Endoscopy guidelines suggest considering surgical resection for duodenal lesions that involve Ͼ33% of the luminal circumference, because of the difficulty of radical endoscopic removal.…”
Section: Discussionmentioning
confidence: 99%
“…Leppiliez and colleagues reported no cases of recurrence although mean follow up in this series was only 15 months and 42% of patients had only had one follow-up endoscopy [Leppiliez et al 2008]. Kim and colleagues also had 0% recurrence after mean 29 months follow up [Kim et al 2010]. Conversely Abbass and colleagues reported 36% recurrence of adenomatous lesions after a mean follow up of 26 months, and noted a greater recurrence rate of 63% in lesions >2 cm in diameter [Abbass et al 2010].…”
Section: Endoscopic Resectionmentioning
confidence: 97%
“…They are usually solitary and the majority are sessile or flat rather than pedunculated [Ahmad et al 2002;Apel et al 2005;Honda et al 2009;Kedia Around 80-94% of SDAs are found in the second part of the duodenum with mean size in various series ranging from 13 to 29 mm [Alexander et al 2009;Apel et al 2005;Honda et al 2009;Kim et al 2010;Lepilliez et al 2008]. Contrast radiography is unreliable in detecting duodenal adenomas, because of the flat or sessile nature of the majority of lesions, and the vast majority are detected during upper gastrointestinal endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Several other authors found an immediate bleeding rate in the same range (6-18%) [3,[9][10][11][12] . In 2 studies, high rates of procedural hemorrhage (57.8 and 43%, respectively) were observed [13,14] , whereas 3 authors did not observe any procedural bleeding complications [2,5,15] . Duodenal perforation occurred in 8 cases among all na Na studies leading to an overall perforation of 1.5% [8,13,[16][17][18] .…”
Section: Review Of the Literaturementioning
confidence: 97%